A low-current LaB6 open-end knife-edge emitter hollow cathode for low-power Hall thrusters. (27th August 2021) - Potrivitu, G-C; Xu, L; Xu, S
Abstract: Heated thermionic cathodes based on LaB6 emitters are known to consume a relatively large amount of power during the heating part of the ignition phase. Miniaturized electric propulsion systems, and in particular low-power Hall thrusters, rely on the operation of self-sustained cathodes at low-current emission, typically below 1 A. At PSAC/SPC, an open-end knife-edge LaB6 emitter hollow cathode was developed and tested, denoted herein as the PSAC-KE cathode. Here, a detailed description of the new model's design and comparison to the older version, the PSAC cathode, is included. Electrostatic simulations suggested that the open-end emitter geometry allowed for an enhanced electric field within the emitter region during cathode startup and steady-state operation as compared to the orificed emitter PSAC cathode. The PSAC-KE cathode's thermal management was improved based on iterative thermal simulations driven by different cathode geometries and various combinations of materials. The new cathode was tested with xenon in diode mode with an external anode and triode mode with the external anode and the keeper electrode. Furthermore, results from the coupling tests with a low-power Hall thruster are presented. Cathode performance was monitored over a range of anode current from 0.1 to 1 A, mass flow rates from 0.057 to 0.3 mg s −1 and keeper current of 0.05, 0.1, and 0.15 A. The cathode's thermal design was assessed with thermocouple measurements and compared with thermal simulations and results obtained for the PSAC cathode. The preliminary tests showed that the PSAC-KE cathode achieved ignition at low heating power below 35 W, self-sustained operation at 1 A when in standalone mode, and <1 A when against a low-power Hall thruster.